2021
DOI: 10.1017/s1366728921000468
|View full text |Cite
|
Sign up to set email alerts
|

Neurophysiology of non-native sound discrimination: Evidence from German vowels and consonants in successive French–German bilinguals using an MMN oddball paradigm

Abstract: The present electroencephalographical multi-speaker MMN oddball experiment was designed to study the phonological processing of German native and non-native speech sounds. Precisely, we focused on the perception of German /ɪ-iː/, /ɛ-ɛː/, /a-aː/ and the fricatives [ʃ] and [ç] in German natives (GG) and French learners of German (FG). As expected, our results showed that GG were able to discriminate all the critical vowel contrasts. In contrast, FG, despite their high L2 proficiency level, were only marginally s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 57 publications
1
0
0
Order By: Relevance
“…English vowel contrasts evoked lower MMN amplitudes in the latter group. This result seems to be further corroborated by Wottawa et al (2022) , who also found a diminished MMN response in proficient German learners who acquired German at school. The apparent discrepancy in the previously obtained results seems to indicate the importance of the learning context as a vital component of non-native phonemic perception.…”
Section: Introductionsupporting
confidence: 70%
“…English vowel contrasts evoked lower MMN amplitudes in the latter group. This result seems to be further corroborated by Wottawa et al (2022) , who also found a diminished MMN response in proficient German learners who acquired German at school. The apparent discrepancy in the previously obtained results seems to indicate the importance of the learning context as a vital component of non-native phonemic perception.…”
Section: Introductionsupporting
confidence: 70%